Aspects of Innate Immunity and Parkinson’s Disease - Huang, Yue; Halliday, Glenda M. (Frontiers in Pharmacology, 2012)
Genetic studies on PARK genes have identified dysfunction in proteasomal, lysosomal and mitochondrial enzymes as pathogenic for Parkinson’s disease (PD). We review the role of these and similar enzymes in mediating innate immune signalling. In particular, we have identified that a number of PARK gene products as well as other enzymes have roles in innate immune signalling as well as DNA repair and regulation, ubiquitination, mitochondrial functioning and synaptic trafficking. PD enzymatic dysfunction is likely to contribute to inadequate innate immune responses to a variety of extra- and intra-cellular stimuli, with a number of the innate immunity related enzymes found in the characteristic Lewy body pathology of PD. The decrease in innate immunity in PD is associated with an increase in markers of adaptive immunity, and recent GWAS studies have identified variants in human leukocyte antigen (HLA) region as associated with late-onset sporadic PD (Hamza et al., 2010;Hill-Burns et al., 2011). Intriguing new data also suggest that peripheral immune responses may be involved, giving some potential to alleviate such peripheral dysfunction more directly in patients with PD. It is now important to identify the cell type specific immune responses contributing to the initial changes that occur in PD, as well as to the propagating immune responses important for the progression of PD pathology between cells and within the brain. Overall, a complex interplay between different types of immunity appear to be involved in the underlying pathology of PD.